Mass-forming chronic invasive fungal sinusitis; an uncommon mimicker of head & neck malignancy. (28th October 2021) - Muldoon, J; Hou, T
Abstract: Introduction/Objective: Invasive fungal sinusitis is a progressive infection affecting the nasal cavity and associated sinus spaces. Acute forms affect immunocompromised patients with debilitating systemic diseases while chronic forms usually occur in immunocompetent individuals. Methods/Case Report: A 26-year-old immunocompetent male with daily Marijuana smoking consulted for acute swelling of the right eye with dull pain, photophobia, loss of vision and pressure of 4 day duration. He reported nasal congestion for approximately one year and over the previous 2 months developed exophthalmos. Imaging demonstrated a 4.9 x 4.3 x 4.1 cm invasive soft tissue mass in the right lamina papyracea with involvement of the paranasal sinus, right orbit, and intracranial space. The mass was presumed to represent a high-grade malignancy. Biopsy was performed and demonstrated granulomatous invasive fungal sinusitis. The patient underwent right orbitotomy and right extranasal ethmoidectomy. He was begun on empiric amphotericin B. After culture and sequencing identification of Curvularia species, voriconazole was added. Follow up imaging studies after two month of treatment still demonstrated residual mass forming lesion with 10-20% decrease in size. The patient has regained his vision after 4 month of treatment and he is expected to complete a six months course. If the mass forming lesion persists, a second round of surgical debridement will be performed. Results (if a Case Study enter NA): N/A Conclusion: Curvularia is a dematiaceous fungus most commonly associated with allergic sinusitis, but can rarely become invasive in immunocompetent individuals. Histopathologically large fungal elements are easily recognizable but specific identification requires culture or ribosomal DNA sequencing by PCR. Mass-forming chronic fungal sinusitis overlaps clinically and radiologically with head and neck malignancies. Our report brings attention to this uncommon clinical variant of invasive fungal sinusitis that affects immunocompetent individuals.